Exemption from Health Care Fees Influences Indications of Caesarean Section in a Urban Health District Hospital in Benin - SOSSA, JÉRÔME CHARLES; SOPOH, GHISLAIN E.; OGOUDJOBI, OGOURINDÉ MATHIEU (My University, 2017)
Rising caesarean birth rates in recent decades are an issue of public health. Potential harms for mothers and newborns are associated with caesarean delivery. Determinants of caesarean birth rates in Benin are unknown. The objective was to assess changes in caesarean rate and compare its indications before and during the implementation of policy of caesarian section fee exemption (PCSFE) in an urban district hospital in Cotonou, Benin. This cross-sectional study conducted at Suru Léré hospital, Cotonou, in 2014. Data on caesarean section were collected from completed medical records of 2104 women who underwent caesarean section before and during the implementation of the PCSFE. Caesarean rates by quarter varied between 17% and 26% (p=0,133) before the PCSFE while the rate increased significantly from 28% to 48% (p<0,001) during the implementation PCSFE. During the period of implementation of PCSFE, frequencies of "placenta prævia" (p = 0.022) and excessive uterine height (p <0.001) were significantly higher while frequencies of "uterine pre-rupture syndromes" (p = 0.017) and generally contracted pelvis (P = 0.013) decreased compared to period prior the PCSFE. Caesarean section rate increased during the implementation PCSFE and some caesarean section indications increased during the PCSFE. Further prospective studies are needed to follow the evolution of indications of caesarean section to inform preventives measures in urban district hospital Suru Léré Cotonou.
Keywords: Fee Exemption Policy; Caesarean Section; Indications; Benin